Use a commutative law to write an equivalent expression to xy + 3z?


2 Answers

Oddman Profile
Oddman answered
The commutative law says the order of operands for addition or multiplication may be reversed without changing the value of the result. Thus, all of the following are equivalent
  xy + 3z
  yx + 3z
  xy + z*3
  yx + z*3
  3z + xy
  z*3 + xy
  3z + yx
  z*3 + yx

I have used the asterisk (*) to indicate multiplication by a following numerical value to avoid ambiguity regarding the meaning of the 3. In other words, many people interpret z3 to mean z^3. Writing it as z*3 removes doubt.
Cody Harghastunion Profile
Xy + 3z (Use any numbers you want for the variables. Lets say X=2, Y=5, Z=3)
2x5 + 3x3
10 + 3x3 (2x5=10)
10 + 9 (3x3=9)
19 (10+9=19)

So if you were to use the commutative property, you would write
2x5 + 3x3=3x3 + 2x5

Answer Question